From persecution to toleration the Glorious Revolution and religion in England - Grell, Ole Peter; Israel, Jonathan I. (Jonathan Irvine), 1946-; Tyacke, Nicholas (Oxford : Clarendon, 1991)
The scholars who contribute to this volume explore a variety of themes, including the nature of religious dissent, the idea of freedom of conscience, and attitudes towards the Huguenot community. They examine not only Protestant dissent, but also Catholicism, Judaism, and Deism.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Religious tolerance -- England -- History -- 17th century -- Congresses; Religion and state -- England -- History -- 17th century -- Congresses; England -- Religion -- 17th century -- Congresses; Great Britain -- History -- 1660-1714 -- Congresses; Great Britain -- History -- Revolution of 1688 -- Congresses